Potential energy (PE ) = m g h
Where:
m = mass = 3800 kg
g = acceleration due gravity = 10 m/s^2
h = heigth = 110 meters
Replacing:
PE = 3800 * 10 * 110 = 4,180,000 J
Answer:
56
Explanation:
I just want the points to be completely honest with you.
A) ![x=\pm \frac{A}{2\sqrt{2}}](https://tex.z-dn.net/?f=x%3D%5Cpm%20%5Cfrac%7BA%7D%7B2%5Csqrt%7B2%7D%7D)
The total energy of the system is equal to the maximum elastic potential energy, that is achieved when the displacement is equal to the amplitude (x=A):
(1)
where k is the spring constant.
The total energy, which is conserved, at any other point of the motion is the sum of elastic potential energy and kinetic energy:
(2)
where x is the displacement, m the mass, and v the speed.
We want to know the displacement x at which the elastic potential energy is 1/3 of the kinetic energy:
![U=\frac{1}{3}K](https://tex.z-dn.net/?f=U%3D%5Cfrac%7B1%7D%7B3%7DK)
Using (2) we can rewrite this as
![U=\frac{1}{3}(E-U)=\frac{1}{3}E-\frac{1}{3}U\\U=\frac{E}{4}](https://tex.z-dn.net/?f=U%3D%5Cfrac%7B1%7D%7B3%7D%28E-U%29%3D%5Cfrac%7B1%7D%7B3%7DE-%5Cfrac%7B1%7D%7B3%7DU%5C%5CU%3D%5Cfrac%7BE%7D%7B4%7D)
And using (1), we find
![U=\frac{E}{4}=\frac{\frac{1}{2}kA^2}{4}=\frac{1}{8}kA^2](https://tex.z-dn.net/?f=U%3D%5Cfrac%7BE%7D%7B4%7D%3D%5Cfrac%7B%5Cfrac%7B1%7D%7B2%7DkA%5E2%7D%7B4%7D%3D%5Cfrac%7B1%7D%7B8%7DkA%5E2)
Substituting
into the last equation, we find the value of x:
![\frac{1}{2}kx^2=\frac{1}{8}kA^2\\x=\pm \frac{A}{2\sqrt{2}}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dkx%5E2%3D%5Cfrac%7B1%7D%7B8%7DkA%5E2%5C%5Cx%3D%5Cpm%20%5Cfrac%7BA%7D%7B2%5Csqrt%7B2%7D%7D)
B) ![x=\pm \frac{3}{\sqrt{10}}A](https://tex.z-dn.net/?f=x%3D%5Cpm%20%5Cfrac%7B3%7D%7B%5Csqrt%7B10%7D%7DA)
In this case, the kinetic energy is 1/10 of the total energy:
![K=\frac{1}{10}E](https://tex.z-dn.net/?f=K%3D%5Cfrac%7B1%7D%7B10%7DE)
Since we have
![K=E-U](https://tex.z-dn.net/?f=K%3DE-U)
we can write
![E-U=\frac{1}{10}E\\U=\frac{9}{10}E](https://tex.z-dn.net/?f=E-U%3D%5Cfrac%7B1%7D%7B10%7DE%5C%5CU%3D%5Cfrac%7B9%7D%7B10%7DE)
And so we find:
![\frac{1}{2}kx^2 = \frac{9}{10}(\frac{1}{2}kA^2)=\frac{9}{20}kA^2\\x^2 = \frac{9}{10}A^2\\x=\pm \frac{3}{\sqrt{10}}A](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dkx%5E2%20%3D%20%5Cfrac%7B9%7D%7B10%7D%28%5Cfrac%7B1%7D%7B2%7DkA%5E2%29%3D%5Cfrac%7B9%7D%7B20%7DkA%5E2%5C%5Cx%5E2%20%3D%20%5Cfrac%7B9%7D%7B10%7DA%5E2%5C%5Cx%3D%5Cpm%20%5Cfrac%7B3%7D%7B%5Csqrt%7B10%7D%7DA)
Given data
*The value of battery voltage is V = 10 V
*The current flows through the resistor is I = 5 A
The formula for the resistor is given by the Ohm's law as
![R=\frac{V}{I}](https://tex.z-dn.net/?f=R%3D%5Cfrac%7BV%7D%7BI%7D)
Substitute the values in the above expression as
I think F= mv²/r
And F=ma
So, ma = mv²/r
a = v²/r
a = 100/5
a = 20 m/s